Copper deficiency-induced anemia is caused by a mitochondrial metabolic reprograming in erythropoietic cells. Issue 2 (25th October 2018) - Jensen, Erik L.; Gonzalez-Ibanez, Alvaro M.; Mendoza, Pierina; Ruiz, Lina M.; Riedel, Claudia A.; Simon, Felipe; Schuringa, Jan J.; Elorza, Alvaro A.
Abstract : Copper deficiency reprograms mitochondrial metabolism, which becomes less oxidative, to favor cell expansion over cell differentiation. Abstract : The lack of copper has been associated with anemia, myelodysplastic syndromes and leukemia as well as with a loss in complex IV activity and an enlarged mitochondrial morphology. Mitochondria play a key role during the differentiation of hematopoietic stem cells by regulating the passage from a glycolytic to oxidative metabolism. The former is associated with cell proliferation and the latter with cell differentiation. Oxidative metabolism, which occurs inside mitochondria, is sustained by the respiratory chain, where complex IV is copper-dependent. We have hypothesized that a copper deficiency induces a mitochondrial metabolic reprogramming, favoring cell expansion over cell differentiation in erythropoiesis. Erythroid progression analysis of the bone marrow of mice fed with a copper deficient diet and of the in vitro erythropoiesis of human CD34+ cells treated with a bathocuproine – a copper chelator – showed a major expansion of progenitor cells and a decreased differentiation. Under copper deficiency, mitochondria switched to a higher membrane potential, lower oxygen consumption rate and lower ROS levels as compared with control cells. In addition, mitochondrial biomass was increased and an up-regulation of the mitochondrial fusion protein mitofusin 2 was observed. Most copper-deficient phenotypes were mimicked by the pharmacological inhibition of complex IV with azide. We concluded that copper deficiency induced a mitochondrial metabolic reprogramming, making hematopoietic stem cells favor progenitor cell expansion over cell differentiation.